Sheikh Kamal International Cricket Stadium: adaptation with the tourist’s city, Cox’s Bazar - Saha, Argha (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2016.